Assessment of Condylar Position and Its Association with Unilateral TMD in Patients with Angle’s Class I, II, and III Malocclusions Using CBCT - Dollchi Mehta; Dhruv Swaminarayan; Nikita Patel; Noor Addeen Abo Arsheed; Narendra Prakash Rai; Ismat Fakhra (Journal of Pharmacy and Bioallied Sciences)
Introduction: With cone beam computed tomography (CBCT) as a diagnostic tool, we compare and analyze the condylar position and its relationship with unilateral temporomandibular disorder (TMD) in patients with Angle’s Class I, II, and III malocclusions. Materials and Methods: The association between TMD and age, gender, vertical condyle position, horizontal condyle position, and steepness of articular eminence in individuals with various malocclusions was examined using 30 CBCT images. Results: The asymptomatic group shared the concentric location of the condyle in their respective mandibular fossae, which is also a typical hallmark of Class II and Class III malocclusion on the left temporomandibular joint. Patients with TMD were more likely to be in the posterior condylar position. In all malocclusions and TMD cases, the condylar head’s vertical position was mostly normal and slightly elevated. All malocclusions and TMD patients had moderate to severe articular eminence steepness. In individuals with TMD and malocclusions, the mesiodistal breadth of was considerable on the left side. Conclusion: Future research should be done with a larger sample size and an emphasis on assessing how the condyle’s location will change after therapy for patients with TMD.